2012
DOI: 10.4103/2229-5178.96722
|View full text |Cite|
|
Sign up to set email alerts
|

Piebaldism: A brief report and review of the literature

Abstract: Piebaldism is a rare autosomal dominant disorder of melanocyte development characterized by a congenital white forelock and multiple symmetrical stable hypopigmented or depigmented macules. We report a family with piebaldism affecting three successive generations and also review the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 17 publications
(13 reference statements)
0
39
0
1
Order By: Relevance
“…Nagao et al (1975), found the depigmented lesion of a case of piebaldism and presents mast cells found in the epidermis by electron microscopic study. In addition, different cases in India, reported by Agarwal & Ojha (2012), were observed in two babies, with a similar distribution of depigmentation in their father, they alike in other piebaldism but did not present in their limbs.…”
Section: Characteristic Of Depigmentation In To Balomentioning
confidence: 79%
See 1 more Smart Citation
“…Nagao et al (1975), found the depigmented lesion of a case of piebaldism and presents mast cells found in the epidermis by electron microscopic study. In addition, different cases in India, reported by Agarwal & Ojha (2012), were observed in two babies, with a similar distribution of depigmentation in their father, they alike in other piebaldism but did not present in their limbs.…”
Section: Characteristic Of Depigmentation In To Balomentioning
confidence: 79%
“…Different types of vitiligo may rarely be present at birth, but is usually acquired later in life, is unstable and is not genetically inherited, although it may run in some families. Based on characteristic of various melanin disorder, thus to person with the appearance, presence of white forelock in the frontal region, typical distribution of depigmented macules, their relative stability since the time of appearance and presence of a similar pattern of depigmented macules in other family members could be confirmed as piebaldism (Agarwal & Ojha, 2012;Park et al, 2014;Bassi et al, 2015). Oiso & Kawada (2012), following by Saleem (2019), found the association of hearing loss and pigment abnormalities results from an abnormal proliferation, survival, migration, or differentiation of neural crest-derived melanocytes.…”
Section: Characteristic Of Depigmentation In To Balomentioning
confidence: 98%
“…It is linked to mutation in C-KIT proto-oncogene mapped to chromosome 4q11/4q12. This gene is responsible for cell surface receptor transmembrane tyrosine kinase for stem cell/mast cell growth factor [3]. There may be Zinc finger neural crest mutation instead.…”
Section: Discussionmentioning
confidence: 99%
“…A piebald patient with congenital dyserythropoietic anemia Type II (HEMPAS) and a patient with Diamond-Blackfan anemia have been also reported. Grover's Disease or transient acantholytic dermatosis limited to the depigmented macules in a patient with piebaldism has been described [6,9,11].…”
Section: Association With Other Disordersmentioning
confidence: 99%
“…Intermediate phenotypes are seen with mutations near the transmembrane region. The classic type of static piebaldism is due to c-kit gene mutations in the vicinity of codon 620 (Val620Ala, 1859T>C) [6,9].…”
Section: Genetics/pathogenesismentioning
confidence: 99%